1993
DOI: 10.1148/radiology.188.2.8327692
|View full text |Cite
|
Sign up to set email alerts
|

Hyperechoic renal cell carcinomas: increase in detection at US.

Abstract: Recent reports have indicated that hyperechoic renal cell carcinomas (RCCAs) are more frequent among small cancers and that small cancers are being detected more frequently. To determine whether these trends have resulted in a change in the frequency of detection of hyperechoic RCCA and, in particular, in the frequency of RCCA mimicking angiomyolipomas (AMLs), the sonographic features of 90 pathologically proved RCCAs in 82 patients were retrospectively reviewed and correlated with tumor size. Tumor echogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(61 citation statements)
references
References 0 publications
3
55
0
3
Order By: Relevance
“…In our experience as well as that of other previous investigators, AML tended to be more echogenic than RCC, 3,7,[8][9][10] and some investigators tried to differentiate these two tumors using echogenicity alone. 3,6 To our knowledge, the most systematic effort so far was made by Siegel and coworkers.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In our experience as well as that of other previous investigators, AML tended to be more echogenic than RCC, 3,7,[8][9][10] and some investigators tried to differentiate these two tumors using echogenicity alone. 3,6 To our knowledge, the most systematic effort so far was made by Siegel and coworkers.…”
Section: Discussionsupporting
confidence: 67%
“…6,7 In our experience as well as that of others, AML tend to be more echogenic than RCC. 3,7,[8][9][10] Some investigators tried to differentiate these two tumors using a visual assessment of echogenicity alone without satisfactory results. 3,6 The purposes of this study were to evaluate the echogenicity of renal masses objectively and quantitatively by using CATEQ technique and to assess the value of this technique in differentiating small hyperechoic RCC from AML.…”
mentioning
confidence: 99%
“…Two AMLs (9.5%) were hypoechoic on gray-scale US in this study. Forman et al (8) reported that approximately 30% of small RCCs appear as hyperechoic, which is how small benign renal masses similarly appear. In the current study, 6% of the benign renal masses were atypically iso-echoic and 29% of those masses were slightly hyperechoic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Forman showed that 77% of small RCCs showed variable echogenicity, and 32% were hyperechoic enough to mimic renal AMLs [31]. Conversely, although AMLs are typically homogenously echogenic, lipid-poor AMLs may appear isoechoic on US [32].…”
Section: Renal Cell Carcinoma and Angiomyolipomamentioning
confidence: 99%